EFEKTIFITAS MODEL PEMBELAJARAN BERBASIS PROYEK PADA MATA KULIAH PENGELOLAAN LABORATORIUM TERHADAP KREATIFITAS MAHASISWA PGMI STIT AL HILAL - Gusti Handayani (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2018)
The purpose of this research is to notice the effectiveness of project-based learning models of the course laboratory management towards students ' creativity PGMI STIT Al-Hilal Sigli. The method used in this research is an experimental method or pre-experiment which was designed using the one-group pretest-posttest. The population were PGMI students of academic year 2015/2016, while the sample in this research is the V semester students taking course of the Laboratory Management I academic year 2015/2016. There were two data collection techniques used in this study, the technique of observation and examination technique. The instruments used in this study i.e., questionnaire, observation sheet and test. The results showed that project-based learning in the laboratory management course is effective against student creativity of PGMI students at Al-Hilal Sigli